Poincaré Plot of Fingertip Photoplethysmogram Pulse Amplitude Suitable to Assess Diabetes Status - Bagus Haryadi; Gen-Min Lin; Chieh-Ming Yang; Shiao-Chiang Chu; Hsien-Tsai Wu (IAES Indonesia Section, 2017)
Multiscale entropy (MSE), an estimate of the complexity of physiological signals has been used for assessing diabetes status. This method requires much computation effort. Our study aimed to examine the Poincaré plot, an easier method for computation to differentiate the diabetes status. We selected subjects and divided them into three groups including the non- diabetes (HbA1c ≤ 6.5%, n=22), diabetes with good control (6.5% < HbA1c < 8%, n=23), and diabetes with poor control (HbA1c ≥ 8%, n=17). Poincaré method used consecutive 250 data points of PPG pulse amplitudes from each subject’s right index fingertip. This method resulted in SSR, the standard deviation of the original photoplethysmogram (PPG) pulse amplitude (SD1) and the standard deviation of the interval 1 PPG pulse amplitude (SD2) ratio. The SSR in the three groups of non-diabetes, diabetes with good control and diabetes with poor control were 0.50, 0.28, and 0.23, respectively and differed between groups (P < 0.05). Our findings suggested that the Poincaré plot of right-hand PPG pulse amplitude may be convenient to evaluate diabetes status.